Anti proliferative effect of Silver Nanoparticles synthesized Using Human Serum Albumin on MCF-7 Cell Line. - V. PRADEEPA,; M. SUJATHA,; T. SRIRAM, (International Journal of Pharma and Bio Sciences, 2017)
A simple and convenient method is synthesis of silver Nanoparticles (AgNps) in a foam matrix using the protein Human serum albumin (HSA) is reported. HAS is an excellent foaming agent and by virtue of its zwitter ionic character at the protein isoelectric point, may be used to bind to cationic silver (Ag+) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver Nanoparticles. The HAS molecules coat and stabilize the Nanoparticles thus eliminating the necessity of employing an additional stabilizing agent in the experimental procedure. The synthesized Nanoparticles where characterized by UV-visible spectroscopy, X-ray diffraction (XRD), Scanning electron microcopy (SEM), energy-dispersive X-ray spectrometry (EDAX) and Fourier-transform infrared spectroscopy (FTI) with silver Nanoparticles of 20-30nm were obtained invitro cytotoxic studies revealed that the silver Nanoparticles shows Significant growth inhibition in dose dependent manner.